Kick Drill for Ironman Training - Woolley, H.
Author shows that and why kick should be an essential part of swim training whether or not you are training for Ironman. An efficient kick is central to your leverage system in swimming therefore if you neglect this important swimming fundamental it will leave a glaring gap in your swimming skills and most certainly affect your overall performance in the water.